PENINGKATAN KETERAMPILAN TENAGA KERJA INDONESIA (TKI) MELALUI PELATIHAN RIAS PENGANTIN - Hidayah, Nurul; Supiani, Titin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract The resource potential of Indonesian migrant workers is relatively low both in terms of knowledge and readiness to work abroad, one of which is in Singapore where it is known that there is limited knowledge and readiness of Indonesian workers in Singapore, so there is a need for counseling and providing skills that are useful for life abroad through activities - Extension activities and skills training. This form of community service activity is counseling and demonstrations of Indonesian bridal make-up to improve the skills of Indonesian workers in Singapore. Bridal makeup artist is a promising job opportunity given the development of the beauty salon industry. This Indonesian bridal make-up training activity is carried out in stages and continuously with several achievement targets that are tailored to the needs, characteristics of the participants and the objectives of the activities to be achieved. The results of this community service activity include: 1) The increasing knowledge and skills of Indonesian migrant workers in Singapore in the field of bridal make-up, based on filling in the instrument regarding indicators of knowledge of bridal make-up, which previously saw participants' knowledge of 72.6% increasing to 85%. 2) achieving satisfaction with Indonesian bridal make-up PKM activities. Abstrak Potensi sumber daya TKW Indonesia relatif rendah baik dari segi pengetahuan dan maupun kesiapan bekerja diluar negeri, salah satunya di Singapura yang diketahui bahwa adanya keterbatasan pengetahuan dan kesiapan para pekerja Indonesia di Singapura sehingga perlunnya penyuluhan dan pembekalan keterampilan yang bermanfaat bagi kehidupan di Luar Negeri melalui kegiatan-kegiatan penyuluhan dan pelatihan keterampilan. Bentuk kegiatan pengabdian kepada masyarakat ini adalah penyuluhan dan demonstrasi tata rias pengantin Indonesia untuk meningkatkan keterampilan pekerja Indonesia di Singapura. Penata rias pengantin menjadi peluang kerja yang cukup menjanjikan mengingat perkembangan industri salon kecantikan. Kegiatan pelatihan tata rias pengantin Indonesia ini dilakukan secara bertahap dan berkelanjutan dengan beberapa target capaian yang disesuaikan dengan kebutuhan, karakteristik pserta penyuluhan serta tujuan kegiatan yang ingin dicapai. Adapun hasil dari kegiatan pengabdian kepada masyarakat ini antara lain: 1) Meningkatnya pengetahuan dan keterampilan pekerja migran Indonesia di Singapura dalam bidang tata rias pengantin, hal ini diketahui berdasarkan pengisian instrumen mengenai indikator pengetahuan tata rias Pengantin, yang sebelumnya pengetahuan peserta sebesar 72,6% meningkat menjadi 85%. 2) tercapainya kepuasan terhadap kegiatan PKM tata rias pengantin Indonesia.